Properties of engineered oil palm composite boards from 32 years-old tree stems - Razak Wahab; Mohammed Abdus Salam; Othman Sulaiman; Mahmud Sudin; Hashim W. Samsi; Mohd Sukhairi Mat Rasat (ARPN, 2013)
The unutilized stems of oil palm trees found in abundant in Malaysia and considered as an agriculture waste were investigated as a possible alternative to future wood. The stems are of no economic importance in their natural form, but once converted into the form of engineered composite boards their properties improved tremendously. This paper highlighted properties of the engineered composite boards made from oil palm stems at four different height positions comprising two portions height and two cross-sectional zones. The engineered boards have shown to have variation in properties when tested for their physical, mechanical and glue delaminating studies. Testing on all the composite boards specimens were done in accordance with the Japanese Agricultural Standard, JAS No. 237: 2003.